Last seen in Havana [large type] - Dovalpage, Teresa, 1966- (Dovalpage, Teresa, 1966- Havana mystery, 2024)
"Newly widowed baker Mercedes Spivey flies from Miami to her native Cuba in 2019 to care for her ailing paternal grandmother. Mercedes's life has been shaped by loss, beginning with the mysterious unsolved disappearance of her mother when Mercedes was a little girl. Returning to Cuba revives Mercedes's hopes of finding her mother as she attempts to piece together the few scraps of information she has. Could her mother still be alive? Thirty-three years earlier, in 1986, an American college student with endless political optimism falls deliriously in love with a handsome Cuban soldier while on a spontaneous visit to the island. She decides to stay permanently, but soon discovers that nothing is as it seems in Havana. The two women's stories proceed in parallel as Mercedes gets closer to the truth about her mother, uncovering shocking family secrets in the process"--